2012
DOI: 10.1039/c1ob06381b
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and mechanistic studies of metal-free transfer hydrogenations applying polarized olefins as hydrogen acceptors and amine borane adducts as hydrogen donors

Abstract: Metal-free transfer hydrogenation of polarized olefins (RR'C=CEE': R, R' = H or organyl, E, E' = CN or CO(2)Me) using amine borane adducts RR'NH-BH(3) (R = R' = H, AB; R = Me, R' = H, MAB; R = (t)Bu, R' = H, tBAB; R = R' = Me, DMAB) as hydrogen donors, were studied by means of in situ NMR spectroscopy. Deuterium kinetic isotope effects and the traced hydroboration intermediate revealed that the double H transfer process occurred regio-specifically in two steps with hydride before proton transfer characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 48 publications
(29 reference statements)
1
34
0
Order By: Relevance
“…The reactivity of i Pr 2 N=BH 2 with Me 2 NH ⋅ BH 3 was also investigated and an equilibrium was observed between i Pr 2 N=BH 2 , Me 2 NH ⋅ BH 3 , i Pr 2 NH ⋅ BH 3 , and Me 2 N=BH 2 (Scheme ) . Berke and coworkers also demonstrated that polarized olefins could act as hydrogen acceptors in the presence of various amine‐boranes (Scheme ) . Although the solvent‐free reaction of 2‐cyclohexylidenemalonitrile with ammonia borane H 3 N ⋅ BH 3 is rapid (at room temperature: <10 min in [D 8 ]THF, 1 h in CD 3 CN, 20 h in C 6 D 6 ), substantially longer reaction times of up to five days were noted with alkyl‐substituted amine‐boranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity of i Pr 2 N=BH 2 with Me 2 NH ⋅ BH 3 was also investigated and an equilibrium was observed between i Pr 2 N=BH 2 , Me 2 NH ⋅ BH 3 , i Pr 2 NH ⋅ BH 3 , and Me 2 N=BH 2 (Scheme ) . Berke and coworkers also demonstrated that polarized olefins could act as hydrogen acceptors in the presence of various amine‐boranes (Scheme ) . Although the solvent‐free reaction of 2‐cyclohexylidenemalonitrile with ammonia borane H 3 N ⋅ BH 3 is rapid (at room temperature: <10 min in [D 8 ]THF, 1 h in CD 3 CN, 20 h in C 6 D 6 ), substantially longer reaction times of up to five days were noted with alkyl‐substituted amine‐boranes.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic studies of hydrogen transfer from amine‐boranes to Berke's polarized olefin and imines, as well as to the aminoborane i Pr 2 N=BH 2 have been reported. In the case of the polarized olefin (H 2 C) 5 C=C(CN) 2 , a step‐wise mechanism was postulated where fast hydride addition was followed by slower proton transfer . In contrast, the H + /H − transfer to imines (RCH=N−Ph, R=electron‐withdrawing group) was proposed to occur through a concerted six‐membered transition state on the basis of DFT calculations .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, labelling studies using NH 3 ⋅BD 3 and ND 3 ⋅BH 3 revealed that the hydric B−H hydrogen is transferred to the most nucleophilic carbon of the C=C double bond through hydroboration, which is in contrast to the expected concerted double hydrogen transfer and suggests that a different mechanism is operative . Kinetic isotope effect studies and intermediate trapping revealed that the olefin hydrogenation occurs in a two‐step process, in which first the hydrogen is transferred by hydroboration, and then a rate‐determining proton transfer from the amine takes place ( 13 , Scheme ) . In addition, it was hypothesized that the generated (solvent‐stabilized) aminoborane NH 2 =BH 2 intermediate is capable of a second double hydrogen transfer to the olefin through transition state 15 , which explains the formation of borazine and polyborazylene.…”
Section: Stoichiometric Dehydrogenationmentioning
confidence: 99%
“…[21] Kinetic isotope effect studies and intermediate trapping revealed that the olefin hydrogenation occurs in at wo-step process, in which first the hydrogen is transferred by hydroboration, and then ar ate-determining proton transfer from the amine takes place (13,S cheme 10). [36] In addition, it was hypothesized that the generated (solventstabilized) aminoborane NH 2 =BH 2 intermediate is capable of a second double hydrogent ransfer to the olefin throught ransition state 15,w hich explainst he formation of borazine and polyborazylene.…”
Section: Dihydrogen Transfer To Organic Càca Nd Càebonds (E = N O P)mentioning
confidence: 99%
“…Next, we probed the fate of 1 theoretically in the presence of Lewis acids B(C 6 F 5 ) 3 and B(C 6 H 5 ) 3 in nondonor solvents such as benzene. There are experimental studies in which the dehydrogenation of 1 is performed in nonpolar solvents such as benzene and toluene . In benzene, both B(C 6 F 5 ) 3 and B(C 6 H 5 ) 3 exist as free Lewis acids as benzene has no donor atom to form a Lewis acid–base adduct.…”
Section: Resultsmentioning
confidence: 99%